Synthesis of Bis-2, 3-dihydroquinazolin-4(1H)-ones and 2, 3-Dihydroquinazolin-4(1H)-ones Derivatives with the Aid of Silica-Supported Preyssler Nanoparticles. (10th September 2013) - Gharib, Ali; Hashemipour Khorasani, Bibi Robabeh; Jahangir, Manouchehr; Roshani, Mina; Safaee, Reza
Abstract : One-pot three-component condensation of isatoic anhydride with primary amines or ammonium carbonate and aromatic aldehydes in refluxing ethanol in the presence of catalytic amounts of silica-supported preyssler nanoparticles (SPNP) afforded the corresponding 2, 3-dihydroquinazolin-4(1 H )-ones in high yields, and bis-dihydroquinazolinones were synthesized for the first time by a novel pseudo-five-component condensation of isatoic anhydride, a primary amine, and a dialdehyde in water. The catalyst is reusable and can be applied several times without any decrease in product yield.